Swift and Complete Healing of Digital Ulcers after Macitentan Treatment - Emilio Giner Serret (Case Reports in Rheumatology)
Digital ulcers are a burdensome and painful condition with sparse options of treatment. We report the case of a 78-year-old female patient with limited cutaneous systemic sclerosis that sequentially developed digital ulcers. After the appearance of digital ulcers in the soles of her feet she was successfully treated with bosentan. The report of two new digital ulcers in her hands 9 months later alongside with elevated transaminase levels led to a switch to macitentan treatment. A swift and complete healing of both digital ulcers was observed after 3 months, with the restoration of normal biochemical values.